Assessment of Symbiotic Effectivenes's of Advanced Generation Mutants of Fenugreek (Trigonella foenum graecum Linn.) Selected for Higher Yield - Dashora, Abhay; Ramkrishna, K; Choudhary, G R; Saini, Navindra (Annals of Arid Zone, 2016)
A study was conducted under controlled conditions to assess symbiotic efficiency of eight advanced generation (M6 to Mg) mutants of fenugreek variety. RMt- L basically selected for higher yield. The mutants significantly differed for the nodule traits. but showed no ditTerence for nitrogen content per plant when inoculated with Rhizobium meliloti FR-9. Also. these mutants did not differ significantly for their ability to use combined nitrogen (20 mM KN03). Two mutants namely 95-2 and 54-3 identitied as nitrate tolerant mutants for nodulation, were evaluated in tield under various regimes of fertilizer nitrogen, ranging from no nitrogen to 60 kg N ha,l. The two mutants were stable for nodulation irrespective ~f application of fertilizer nitrogen. While mutant 54-3 out-yielded parent and mutant 95-2. the biologi'cal yield of the three host genotypes was statistically at par.